Pelatihan Digital Marketing untuk Meningkatkan Kapasitas Pemasaran UMKM di Koto Kociak Kabupaten Lima Puluh Kota - Yindrizal Yindrizal; Fatma Poni Mardiah; Alfitman Alfitman; Nur Ari Sufiawan; Nadia Fazira (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Micro, Small, and Medium Enterprises (MSMEs) constitute a key economic sector with substantial contributions to national growth. Advances in information technology and the internet have brought significant changes to marketing strategies, shifting traditional offline methods toward digital, online-based approaches. This transformation necessitates adaptation to maintain competitiveness in an increasingly dynamic market environment. In Koto Kociak, local MSMEs primarily operate in snack production (e.g., ganepo, rendang, and other cassava-based products) and handicraft sectors such as knitting. The purpose of this community engagement program was to provide outreach and training on the use of digital marketing as a feasible and contextually relevant strategy for MSME marketing enhancement. The methods applied included preliminary observations and interviews to identify participants’ needs, followed by lectures and discussions, as well as demonstrations and hands-on practice in utilizing digital platforms. The results indicated an improvement in participants’ understanding of digital marketing strategies, particularly in leveraging social media and online platforms to expand market reach. Moreover, participants reported that digital marketing offers a cost-effective and accessible means of promoting local products. These findings suggest that digital marketing outreach supports the shift from traditional to digital-based marketing practices among MSMEs. Continued mentoring and collaboration with local government are recommended to ensure sustainable implementation and to strengthen long-term economic outcomes for local communities.